The Influence of Credit Risk Using Derivative Financial Instruments on the Performance Commercial banks - Jabbar Mohammed*, Muna (Journal of Economics and Administrative Sciences, 2024)
The research aims to reveal the influence of credit risks using Derivative Financial Instruments (DFIs) on the financial performance of commercial banks in Iraq. To achieve the research aim and test its main hypothesis, a questionnaire is distributed to listed commercial banks in the Iraq Stock Exchange and that apply DFIs. The researcher used the questionnaire as the main tool in collecting data. Financial data of the variables of the study are analysed by a simple regression method, the arithmetic mean(AM) and standard deviation. The study used the statistical program (SPSS ) to analyse the data. The research sample consisted of (70) questionnaire forms that were distributed and (68) valid forms were recovered. Research results show that using DFIs reduces exposure to interest rate risks, exchange rates and price fluctuations. The financial crisis is the result of the excessive use of financial derivatives outside regulatory restrictions and securitization to collect liquidity. Financial derivatives represent the fastest-growing form of financial transactions and continue to grow even in crisis conditions. DFIs help to identify risks associated with economic losses incurred by the economic unit as a result of weaknesses in the management and operation of derivatives contracts. Accounting profit-based performance indicators, such as return on assets, return on property rights, earnings per share and cash flows per share, contribute to the evaluation of performance, as well as the use of DFIs contribute to increasing profits. The study shows that credit risks using DFIs have a significant positive influence on performances financial in commercial banks in Iraq.Paper type: Research paper.